Early different cognitive processes evoked by carnival vs. general promotions when shopping online: An ERPs study - Han, Wei; Zhang, Xuefeng (Frontiers in Neuroscience, 2023)
This study aims to investigate cognitive processes to an unknown e-commerce platform after exposure to carnival and general promotion activities using event-related potentials. The booming development of online shopping has intensified market competition. In addition to general sales promotions, online shopping has introduced new changes including artificial carnival promotions. Thirty-three participants were recruited in this study to probe how consumers perceive carnival and general promotion information using event-related potentials (ERPs). Carnival or general promotion posters were presented first, then an unknown e-commerce platform brand was presented in the second stage, at which time the subjects' cognitive process to the brand were observed in an implicit paradigm. The results showed that after priming with carnival promotion posters, the unknown e-commerce platform stimuli elicited larger P2 and N2 components than were observed after the presentation of general promotion posters; however, the P3 component did not show a significant difference. These findings indicate that the target identification and cognitive control mechanism with regard to an unknown e-commerce platform are likely influenced by the implicit memory of different promotion activities when shopping online. The results suggest that ERP components may have the potential to be employed as indices to estimate the effectiveness of promotion methods for an unknown brand.